Synthesis and Application of Fe3O4–ZrO2 Magnetic Nanoparticles for Fluoride Adsorption from Water - Israel Águila-Martínez; José Antonio Pérez-Tavares; Efrén González-Aguiñaga; Pablo Eduardo Cardoso-Avila; Héctor Pérez Ladrón de Guevara; Rita Patakfalvi (Inorganics)
This study presents the synthesis, characterization, and application of magnetic magnetite–zirconium dioxide (Fe3O4–ZrO2) nanoparticles as an efficient nanoadsorbent for fluoride removal from water. The nanoparticles were synthesized using a wet chemical co-precipitation method with Fe/Zr molar ratios of 1:1, 1:2, and 1:4, and characterized using Fourier-transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy-dispersive X-ray spectroscopy (EDS). FTIR analysis confirmed the presence of Fe3O4 and ZrO2 functional groups, while XRD showed that increased Zr content led to a dominant amorphous phase. SEM and EDS analyses revealed quasi-spherical and elongated morphologies with uniform elemental distribution, maintaining the designed Fe/Zr ratios. Preliminary adsorption tests identified the Fe/Zr = 1:1 (M1) nanoadsorbent as the most effective due to its high surface homogeneity and optimal fluoride-binding characteristics. Adsorption experiments demonstrated that the material achieved a maximum fluoride adsorption capacity of 70.4 mg/g at pH 3, with the adsorption process best fitting the Temkin isotherm model (R2 = 0.987), suggesting strong adsorbate–adsorbent interactions. pH-dependent studies confirmed that adsorption efficiency decreased at higher pH values due to electrostatic repulsion and competition with hydroxyl ions. Competitive ion experiments revealed that common anions such as nitrate, chloride, and sulfate had negligible effects on fluoride adsorption, whereas bicarbonate, carbonate, and phosphate reduced removal efficiency due to their strong interactions with active adsorption sites. The Fe3O4–ZrO2 nanoadsorbent exhibited excellent magnetic properties, facilitating rapid and efficient separation using an external magnetic field, making it a promising candidate for practical water treatment applications.